Correlation between extraintestinal manifestations and clinical parameters with the histologic activity index in patients with inflammatory bowel diseases - Štulić, Miloš; Ćulafić, Djordje; Mijač, Dragana; Janković, Goran; Jovičić, Ivana; Krstić, Miodrag; Milosavljević, Tomica (Vojnosanitetski pregled, 2017)
Bacground/Aim. Crohn’s disease (CD) and ulcerative colitis (UC) are chronic, idiopathic, inflammatory diseases of the digestive tract. The aim of this study was to determine a possible correlation between the clinical parameters of the disease activity degree and the presence of extraintestinal manifestations with disease activity histopathological degree, in patients presented with CD and UC. Methods. This cross-sectional study included 134 patients (67 with CD and UC, respectively) treated at the Clinic of Gastroenterology, Clinical Center of Serbia, Belgrade. After clinical, laboratory, endoscopic, histopathologic and radiologic diagnostics, the patients were divided into two groups according to their histopathological activity. The group I comprised 79 patients whose values of five-grade histopathological activity were less than 5 (45 with CD and 34 with UC), while the group II consisted of 55 patients with the values higher than 5 (22 with CD and 33 with UC). The CD activity index (CDAI) and Truelove and Witts’ scale of UC were used for clinical evaluation of the disease activity. Results. CD extraintestinal manifestations were present in 28.9% and 63.6% of the patients in the groups I and II, respectively (p < 0.05). Comparison of the mean CDAI values found a significant difference between these two patients groups (the group I: 190.0 ± 83.0, the group II: 263.4 ± 97.6; p < 0.05). No correlation of extraintestinal manifestations of the disease, Truelove and Witts’ scale and histological activity was found in UC patients (p > 0.05). Conclusion. In the patients presented with CD, the extraintestinal manifestations with higher CDAI suggested a higher degree of histopathological activity. On the contrary, in the UC patients, Truelove and Witts’ scale and extraintestinal manifestations were not valid predictors of the disease histopathological activity.